Subclinical hypothyroidism and cognitive function in people over 60 years: a systematic review and meta-analysis - Akintola, Abimbola A.; Jansen, Steffy; van Bodegom, David; van der Grond, Jeroen; Westendorp, Rudi; de Craen, Anton; Van Heemst, Diana (Frontiers in Aging Neuroscience, 2015)
Subclinical hypothyroidism (SCH), defined as elevated thyroid stimulating hormone and normal thyroid hormone levels, and cognitive impairment are both common in older people. While the relation between overt hypothyroidism and cognitive impairment is well established, data on the association between SCH and cognitive impairment are conflicting. This systematic review and meta- analysis was performed to assess available evidence on the association of SCH with cognition in community dwelling, relatively healthy older adults. PubMed, EMBASE, Web of Science, COCHRANE, CINAHL, PsycINFO and Academic Search Premier (January 1966 to April 1, 2015) were searched without language restrictions, as were references of key articles, for studies on the association between SCH and cognition in older adults (>60 years). These studies were reviewed by two independent reviewers according to predefined criteria for eligibility and methodological quality, and data extracted using standardized forms. Of the 844 reports initially identified, 270 remained after exclusion of duplicates. Of the 270, fifteen studies comprising 19, 944 subjects, of whom 1, 199 had subclinical hypothyroidism were included. Data from the 15 studies was pooled, and meta- analyzed cross-sectionally for global cognition (MMSE), executive function, and memory, using random effects models. Pooled effect size (ES) for MMSE was -0.01 (95% CI -0.09, 0.08), with heterogeneity (I2) of 55.1%. Pooled ES was <0.001 (95% CI -0.10, 0.09) for executive function (I2 = 13.5%), and 0.01 (95% CI -0.12, 0.14) for memory (I2 = 46.9%). In addition, prospective analysis including four studies showed pooled ES of 0.033 (95% CI -0.001-0.067) for MMSE (I2 <0.001%), indicating that subclinical hypothyroidism was not significantly associated with accelerated cognitive decline. This systematic review and meta-analysis provides no evidence that supports an association between SCH and cognitive impairment in relatively healthy older adults.